Quantitative analysis of mineral content in enamel using synchrotron microtomography and microhardness analysis. - art. no. 631824 - Delbem, Alberto Carlos Botazzo [UNESP]; Vieira, A. E. M.; Sassaki, K. T.; Cannon, M. L.; Stock, S. R.; Xiao, X.; DeCarlo, F. (Spie - Int Soc Optical Engineering, 2006)
Synchrotron microtomography is a tool to quantify the mineralization of dental tissues as well as microhardness analysis, since they provide adequate precision and contrast sensitivity. This study evaluates synchrotron microtomography and microhardness analysis for quantifying the mineral content of bovine enamel. Fifty enamel blocks were submitted individually for 5 days to a pH-cycling model at 37 degrees C and remained in the remineralizing solution for 2 days. The blocks were treated twice daily for 1 min with NaF dentifrices (Placebo, 275, 550, 1,100 mu g F/g and Crest (R)) diluted in deionized water. Surface microhardness changes (%SMH) and mineral loss (Delta Z) were then calculated. Synchrotron microtomography was also used to measure total mineral lost (SMM). Pearson's correlation (p < 0.05) was used to determine the relationship between different methods of analysis and dose-response between treatments. Dentifrice fluoride concentration and %SMH and Delta Z were correlated (p < 0.05). There was a positive relationship (p < 0.05) when comparing SMM vs. Delta Z; a negative relationship (p < 0.05) was found for %SMH vs. SMM and %SMH vs. Delta Z. Based on the results of this study, it was possible to conclude that synchrotron microtomography provides the best spatial resolution and contrast sensitivity for quantifying mineral gradients.
Keywords: enamel; synchrotron microtomography; microhardness